Political ignorance and the internet - Irene Bertschek; David F. Müller (Journal of Economics and Statistics, 2023)
We examine the link between Internet usage and political ignorance. To do so, we construct a novel index measuring individuals' indifference with respect to political issues, which determines the degree of individual political ignorance. Our descriptive econometric analysis is based on a rich dataset consisting of six surveys of individuals covering the time period 2001–2014 and being representative for the German electorate. The empirical results show that in earlier years of Internet diffusion, there is a negative link between using the Internet and political ignorance. This link changes sign in later years of Internet diffusion. We discuss potential explanations of this observed change in the link such as information overload and the increase in heterogeneity of Internet users.
Keywords: D80; O33; 330; indifference index; information cost; Internet; political ignorance